The use of routine outcome measures in two child and adolescent mental health services: a completed audit cycle - Hall, Charlotte L.; Moldavsky, Maria; Baldwin, Laurence; Marriott, Michael; Newell, Karen; Taylor, John; Sayal, Kapil; Hollis, Chris (BioMed Central, 2013)
Background: Routine outcome measurement (ROM) is important for assessing the clinical effectiveness of health services and for monitoring patient outcomes. Within Child and Adolescent Mental Health Services (CAMHS) in the UK the adoption of ROM in CAMHS has been supported by both national and local initiatives (such as government strategies, local commissioning policy, and research).